The Model of Talent Management Implementation in the Government of Agam Regency - Sri Wahyuni; Septiana Dwi Putrianti; Teni Lestiani; Abdul Rahman (The Future of Education Journal, 2025)
Talent management has become one of the key elements in creating a professional, adaptive, and competitive bureaucracy in the era of Industry 4.0. As part of the merit system, talent management aims to ensure that Civil Servants (ASN) have the competence and optimal performance to support the achievement of national development goals. This study aims to analyze the implementation of talent management in the Government of Agam Regency, identify the factors influencing it, and formulate an appropriate implementation model. Talent management is a crucial part of the merit system to create professional and competitive Civil Servants (ASN). However, the implementation of talent management in the Government of Agam Regency still faces various challenges, such as limited resources, low understanding of the talent management concept, and inadequate supporting infrastructure. Additionally, the research findings also indicate that other influencing factors include the lack of leadership commitment, budget limitations, and policies that have not been consistently implemented.